Development of Positron Emission Tomography (PET) Radiotracers for the GABA Transporter 1 (GAT-1) - Sowa, Alexandra R. (ACS Chem Neurosci, 2018)
In vivo PET imaging of the γ-aminobutyric acid (GABA) receptor complex has been accomplished using radiolabeled benzodiazepine derivatives, but development of specific presynaptic radioligands targeting the neuronal membrane GABA transporter type 1 (GAT-1) has been less successful. The availability of new structure-activity studies of GAT-1 inhibitors and the introduction of a GAT-1 inhibitor (tiagabine, Gabatril(®)) into clinical use prompted us to reinvestigate the syntheses of PET ligands for this transporter. Initial synthesis and rodent PET studies of N-[(11)C]methylnipecotic acid confirmed the low brain uptake of that small and polar molecule. The common design approach to improve blood-brain barrier permeability of GAT-1 inhibitors is the attachment of a large lipophilic substituent. We selected an unsymmetrical bis-aromatic residue attached to the ring nitrogen by a vinyl ether spacer from a series recently reported by Wanner and coworkers. Nucleophilic aromatic substitution of an aryl chloride precursor with [(18)F]fluoride was used to prepare the desired candidate radiotracer (R,E/Z)-1-(2-((4-fluoro-2-(4-[(18)F]fluorobenzoyl)styryl)oxy)ethyl)piperidine-3-carboxylic acid ((R,E/Z)-[(18)F]10). PET studies in rat showed no brain uptake, which was not altered by pretreatment of animals with the P-glycoprotein inhibitor cyclosporine A, indicating efflux by Pgp was not responsible. Subsequent PET imaging studies of (R,E/Z)-[(18)F]10 in rhesus monkey brain showed very low brain uptake. Finally, to test if the free carboxylic acid group was the likely cause of poor brain uptake, PET studies were done using the ethyl ester derivative of (R,E/Z)-[(18)F]10. Rapid and significant monkey brain uptake of the ester was observed, followed by a slow washout over 90 minutes. The blood-brain barrier permeability of the ester supports a hypothesis that the free acid function limits brain uptake of nipecotic acid-based GAT-1 radioligands, and future radiotracer efforts should investigate the use of carboxylic acid bioisosteres.